Stock Composition of the Historical New York Bight Atlantic Sturgeon Fishery Revealed through Microsatellite Analysis of Archived Spines. Issue 6 (7th December 2021) - White, Shannon L.; Johnson, Robin; Lubinski, Barbara A.; Eackles, Michael S.; Secor, David H.; Kazyak, David C.
Abstract: A targeted commercial fishery for Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus once operated in the New York Bight, where it was assumed that most harvested Atlantic Sturgeon were natal to the Hudson River population. However, more recent evidence suggests that the fishery may have been targeting a mixed‐stock aggregation, in which case harvested Atlantic Sturgeon could have been comprised of individuals from multiple populations throughout the species' range. Although there is now a moratorium on Atlantic Sturgeon harvest in the New York Bight, modern molecular approaches provide an opportunity to use archived tissues to perform a retrospective mixed‐stock analysis on the fishery. Genomic DNA extracted from archived fin spines from 80 Atlantic Sturgeon collected nearly 30 years ago suggests that the fishery primarily harvested individuals from the Hudson River population. However, based on individual‐based assignment tests, our results indicate that the fishery also harvested individuals from at least eight other populations located throughout the species' range. This study highlights how archival hard parts that were previously used for age and growth analyses can be employed for retrospective genetic analyses. Further, because the New York Bight harbors relatively high concentrations of Atlantic Sturgeon, the study shows how localized management decisions can influence Atlantic Sturgeon conservation at rangewide scales. When integrated with more recent knowledge of species ecology, these analyses can be used to evaluate the efficacy of previous management strategies and understand the effects of historical processes on contemporary demography.